Analysis of the Contents of the Cleanliness Campaign in the Kompas TV article “Blitar Police Car Turned into a Mask Waste Bank” - Sari, Yoana Puspita; Savitri, Hikmawati Fadjri Devi (Prosiding University Research Colloquium, 2021)
The The COVID-19 pandemic requires people to comply with health protocols, one of whichis wearing a mask. The use of masks is part of a comprehensive series of prevention andcontrol measures that can limit the spread of the virus. The increasing amount of maskwaste and the absence of waste management have a negative impact on environmentalhygiene and health. Seeing this case, it is necessary to carry out a mask waste managementcampaign. The purpose of this study was to analyze the contents of the hygiene campaignin the Kompas TV article "Blitar Police Car Turned into a Mask Waste Bank". This studyuses a qualitative content analysis method. Data collection techniques through primarydata collection from literature studies through journals, articles, and news. The dataanalysis technique used content analysis techniques. The results of the study are in theform of content analysis on the contents of the Kompas TV article cleanliness campaign"Blitar Police Car Turned into a Mask Waste Bank", in the form of different sentenceelements in it. This is a hygiene campaign that is being pursued as an effort to reduce theamount of APD waste, especially masks that are scattered and thrown away carelessly..